Increasing Awareness of Washing Hands with Clean Water During the Bubble Tourism Period of the Covid-19 Pandemic at Doctor Nueng Intercare Krabi School, Thailand 2022: Peningkatan Kesadaran Cuci Tangan Dengan Air Bersih Pada Masa Bubble Tourism Pandemi Covid-19 Di Doctor Nueng Intercare Krabi School, Thailand 2022 (JURNAL UNEJ, 2023)
Covid-19 is a virus that has claimed many lives around the world, from infants to the elderly who are vulnerable to this virus. The surge in Covid-19 was very unexpected, therefore everyone is encouraged to always follow health protocols to prevent the virus from spreading, such as holding a Lock Down where the whole world closes its country to foreign travel and vice versa. After 2 years of the pandemic, several countries have finally reopened their tourist areas to boost the country's economy, such as in Krabi, Thailand. Krabi is a destination for foreign tourists, and among these countries it is considered that Covid-19 has subsided and almost all tourists do not wear masks while traveling. In order to protect oneself from the Covid-19 virus, an educational method is carried out by counseling using educational videos about Bubble Tourism and posters. From the educational results, students understand about Covid-19 Prevention but they feel safe because of herd immunity.